Analysis of Factors Associated with Stunted Growth in Children Aged 12-60 Months Living in Lenda Village, Manggarai Regency, NTT - Ningsih, Oliva Suyen; Jakri, Yohanes; Cahyani, Erika Nur (Jurnal Keperawatan Soedirman, 2020)
Stunting is one of the main health problems in Indonesia resulting from poor nutrition. Stunted growth can have a negative impact on children's development and long-term growth. The prevalence of stunted growth in NTT Province in 2017 reached 22.30%. Lenda Village became the priority village for an integrated stunted growth prevention program in 2018. The purpose of this study was to determine the factors associated with the incidence of stunted growth in children aged 12-60 months (n = 82) in Lenda Village, from October 2018-April 2019 using a cross-sectional study. The sample technique used was purposive sampling.The instruments used were: a questionnaire (including demographic data, birth history, diarrhea, motherâ€™s knowledge), microtoise and weight scales.The analysis data involved a chi-square test and binary logistic regression. The results showed that most children were stunted (58 children (70.7%)). There was a significant associationÂ  between exclusive breastfeeding (AOR = 5.193, 95 % CI= 1.275-21.158, p = 0.022), immunization status (AOR= 0.110, 95 % CI = 0.025-0.477, p =0.003), diarrhea (AOR = 13.386, CI 95 % = 2.270-78.949, p= 0.004), knowledge (AOR = 0.049, 95 % CI = 0.008-0.290, p= 0.001) and stunted growth. Integrated stunted growth management needs to be provided through cross-sectoral collaboration to increase the coverage of health care providers, improve sanitation, increase the level of maternal knowledge and improve health outcomes during both antenatal and postnatal care